(untitled) (World of finance, 2019)
Introduction. Development bank loans for environmental projects in Ukraine must be based on understanding and evaluating the increased risks that they objectively characteristic that may be attributed to unusual risks. An important element of financial security implementation of environmental policy should be the insurance of environmental risks. Environmental situation requires an expansion of traditional as well as search and introduction of new types of insurance, including insurance operating environmental projects from the risk of failure to achieve certain environmental effects. Purpose. Substantiate need for credit insurance and environmental measures as additional tools extrabudgetary funding projects to preserve the environment. Results. The theoretical and methodological approaches to project environmental security, based on insurance against the risk of inability to achieve projected environmental effects, based on the principles of mutual benefit and economic interest of the insured in improving their own environmental safety and to determine the damages as compensation for the losses incurred in connection ‘connection with failure to insured stated in the implementation of environmental projects. Conclusion. It is noted that the important criteria for evaluation of banking risks in this sector are: compliance with Environmental Project national, regional, sectoral objectives and development programs; scientific and technical level of the project; quality of corporate and regional management in the field of environmental protection.